Mixed-mode I/II fracture criteria for adhesively-bonded pultruded GFRP/steel joint. (1st January 2021) - Jiang, Zhengwen; Fang, Zhi; Yan, Libo; Wan, Shui; Fang, Yawei
Abstract: The pure mode-I, pure mode-II and the mixed-mode I/II fracture behavior of the adhesively-bonded pultruded GFRP/steel joint were experimentally investigated by using double cantilever beam (DCB) test, and four-point end-notched flexure (4ENF) test combined with four-point single leg bending (4SLB) test, respectively. The extended global method (EGM) was employed to obtain closed-form analytical solutions of mode-II fracture toughness for the 4ENF specimen and mixed-mode I/II fracture toughness components for the 4SLB specimen. Combined with the mode-I fracture toughness obtained by the experimental compliance method (ECM), the power law criteria in initiation and propagation processes were developed for adhesively-bonded pultruded GFRP/steel joint. Validation on the developed mixed-mode fracture criteria was performed through employing it to predict the load-displacement responses of the 4SLB specimens combined with VCCT. Finally, the mixed-mode fracture criteria of the adhesively-bonded GFRP/steel joint were compared to those of the adhesively-bonded GFRP/GFRP joint for quantifying their difference.